Clinical and Autoimmune Profile of Scleroderma Patients from Western India. (19th October 2014) - Pradhan, Vandana; Rajadhyaksha, Anjali; Nadkar, Milind; Pandit, Pallavi; Surve, Prathamesh; Lecerf, Maxime; Bayry, Jagadeesh; Kaveri, Srinivas; Ghosh, Kanjaksha
Abstract : Background . Systemic sclerosis (SSc, scleroderma) is a disorder characterized by fibrosis of skin and visceral organs. Pathogenesis of scleroderma is complex and is incompletely understood as yet. Autoantibodies in SSc represent a serologic hallmark which have clinical relevance, with diagnostic and prognostic potential. Objectives . To study distribution of clinical manifestations and to identify frequency of autoantibodies among subtypes of scleroderma patients from Western India. Methodology . One hundred and ten scleroderma patients were clinically classified according to the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) criteria. All these patients were in active stage of disease. Clinical manifestations were recorded at the time of presentation. Autoantibodies were tested in them by indirect immunofluorescence test and ELISA. Immunoglobulin levels were estimated by nephelometer. These parameters were further correlated with clinical presentation of the disease. Results . Scleroderma patients had M : F ratio of 1 : 10 where mean age at evaluation was 34.7 ± 10.7 years and a mean disease duration was 43.7 ± 35 months. Clinical subtypes showed that 45 patients (40.9%) had diffused cutaneous (dcSSc) lesions, 32 patients (29.1%) had limited cutaneous (lcSSc) lesions, and 33 patients (30%) had other autoimmune overlaps. The overall frequency of ANA in SSc patients studied was 85.5%. The frequency of anti-Scl70, anti-centromere, anti-endothelial cell antibodies (AECA), and anti-keratinocyte antibodies (AKA) was 62.7%, 22.7%, 30%, and 40.9%, respectively. Anti-Scl70 antibodies were significantly high (75.6% versus 46.9%) among dcSSc patients (P < 0.0115 ) whereas anti-centromere antibodies were significantly high (9% versus 38%) among lcSSc patients when these two subtypes were compared (P < 0.0044 ). Conclusion . This study supports that there are geoepidemiological variations among scleroderma patients for their clinical presentation, autoantibody profile, and immune parameters across the country.